Severe acute respiratory distress syndrome in a patient with AIDS successfully treated with veno‐venous extracorporeal membrane oxygenation: a case report and literature review. Issue 4 (19th August 2018) - Obata, Reiichiro; Azuma, Kazunari; Nakamura, Itaru; Oda, Jun
Abstract : Case: Several successful uses of extracorporeal membrane oxygenation (ECMO) for acute respiratory distress syndrome in patients with novel HIV/AIDS infection have been reported; however, the therapeutic keys have not always been discussed. A 47‐year‐old man was admitted with progressive shortness of breath. He was in respiratory failure with a PaO2 /FI O2 ratio of 110.8 requiring intubation. Chest computed tomography showed diffuse ground glass opacities. An HIV infection was suspected, and a diagnosis of acute respiratory distress syndrome was made. Based on clinical indications, treatment for Pneumocystis jirovecii pneumonia and concomitant bacterial infection was started. Outcome: Despite broad‐spectrum antibiotics, the patient's oxygenation deteriorated, necessitating ECMO. After 19 days of ECMO therapy, the patient was successfully decannulated and was eventually discharged. Conclusion: In acute respiratory distress syndrome in patients with HIV/AIDS refractory to treatment, ECMO should be considered. Post‐ECMO antiretroviral therapy could improve outcomes. Abstract : Extracorporeal membrane oxygenation enabled adequate oxygenation in treatment for acute respiratory distress syndrome with HIV/AIDS.